2017
DOI: 10.1016/j.theriogenology.2017.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of undifferentiated spermatogonia and the spermatogonial niche in the lambari fish Astyanax altiparanae

Abstract: Undifferentiated type A spermatogonia are the foundation of fish spermatogenesis. This cell population includes the spermatogonial stem cell population, which is able to either self-renew or differentiate into cells that will generate the male gamete - the spermatozoa. Spermatogonia stem cells are located in a specific region of the testes known as the spermatogonial niche, which regulates spermatogonial stem cell function. This study characterizes undifferentiated type A spermatogonia and their S-phase label-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These observations suggest that the androgens; growth factors; and vascular supplies of oxygen, nutrients, and hormones may play essential roles in SSC maintenance and self-renewal vs. differentiation in the fish testis niche [10,21]. With respect to whether spermatogonia display a preferential distribution within the fish testes, studies of zebrafish [22] and Astyanax altiparane [45] have shown that both Aund* and Aund spermatogonia are located near the interstitial compartment, in contact with androgen-producing Leydig cells and blood vessels (Figure 4A,B,C). These observations suggest that the androgens; growth factors; and vascular supplies of oxygen, nutrients, and hormones may play essential roles in SSC maintenance and self-renewal vs. differentiation in the fish testis niche [10,21].…”
Section: Spermatogonial Stem Cell Nichementioning
confidence: 99%
“…These observations suggest that the androgens; growth factors; and vascular supplies of oxygen, nutrients, and hormones may play essential roles in SSC maintenance and self-renewal vs. differentiation in the fish testis niche [10,21]. With respect to whether spermatogonia display a preferential distribution within the fish testes, studies of zebrafish [22] and Astyanax altiparane [45] have shown that both Aund* and Aund spermatogonia are located near the interstitial compartment, in contact with androgen-producing Leydig cells and blood vessels (Figure 4A,B,C). These observations suggest that the androgens; growth factors; and vascular supplies of oxygen, nutrients, and hormones may play essential roles in SSC maintenance and self-renewal vs. differentiation in the fish testis niche [10,21].…”
Section: Spermatogonial Stem Cell Nichementioning
confidence: 99%
“…They are commonly found in rivers, lakes, and reservoirs throughout South America [21,22]. The lambari rosa (Astyanax altiparanae) is a species widely used as an experimental model in the fields of biology, ecotoxicology, and reproductive physiology [23][24][25], since its anatomical and behavioral characteristics allow for an interesting comparison with other similar species. In the laboratory, they have characteristics such as ease of handling, acceptance of artificial feeding, prolificacy, and a fast life cycle (reaching the adult stage in around ten weeks) [22,26].…”
Section: Introductionmentioning
confidence: 99%
“…A . altiparanae have been used as a model to study reproductive biology (Abreu et al, 2021; Cassel, Chehade, et al, 2017; Cassel, de Paiva Camargo, et al, 2017; Chehade et al, 2020; Costa et al, 2014; De Paiva Camargo et al, 2017; Gomes et al, 2013; Jesus et al, 2017); however, few studies focused on applying physiological tools to enhance the production of this fish species (Brambila‐Souza et al, 2019).…”
Section: Introductionmentioning
confidence: 99%